PERILAKU MEROKOK DAN KEJADIAN HIPERTENSI DI DESA NOONGAN, KABUPATEN MINAHASA - Mondigir, Suwinglie; Rumampuk, Vonny; Oroh, Cindi (Lasalle Health Journal, 2022)
Background: Smoking behaviour is one of the factors of hypertension. Hypertension is a non-communicable disease that affects 26.4% of the world's population and is the number one cause of death in the world every year. Smoking behaviour has become a people's lifestyle that can provide a risk factor for hypertension. Objective: This study aims to determine the relationship between smoking behaviour with the incidence of hypertension. Methods: This study uses a quantitative approach, using a cross sectional design. The research location was carried out in Noongan Village, Minahasa Regency. The population are who have smoking behaviour dan have a hypertension. The sampling method used purposive sampling method n = 57 respondents. The instrument used was a questionnaire on the behavior of smoking behaviour and a questionnaire on the incidence of hypertension to measure the incidence of hypertension. Results: The results of data analysis using thetest spearman rank found p-value = 0.000 <0.05. Conclusion: There is a significant relationship between the smoking behavior with the incidence of hypertension